Schistosoma mansoni FES Tyrosine Kinase Involvement in the Mammalian Schistosomiasis Outcome and Miracidia Infection Capability in Biomphalaria glabrata - Tavares, Naiara Clemente; Gava, Sandra Grossi; Torres, Gabriella Parreiras; de Paiva, Clara Ênia Soares; Moreira, Bernardo Pereira; Lunkes, Felipe Miguel Nery; Montresor, Langia Colli; Caldeira, Roberta Lima; Mourão, Marina Moraes (Frontiers in Microbiology, 2020)
Schistosomiasis is a neglected tropical disease (NTD) caused by helminthes from the Schistosoma genus. This NTD can cause systemic symptoms induced by deposition of parasite eggs in the host liver, promoting severe complications. Functional studies to increase knowledge about parasite biology are required for the identification of new drug targets, since the treatment is solely based on praziquantel administration. Protein kinases are important for cellular adaptation and maintenance of organisms homeostasis, thus are considered good drug targets for many pathologies. Accordingly, protein kinases are also important for Schistosoma mansoni, as the parasite relies on specific environmental signals to develop into different stages. However, the specific roles of protein kinases in S. mansoni biology are not well understood. This work aims at investigating the Tyrosine-protein kinase FES (Feline Sarcoma) functions in the maintenance of S. mansoni life cycle, especially in the establishment of mammalian and invertebrate hosts' infection. In this regard, the verification of SmFES expression among S. mansoni stages showed that SmFES is more expressed in infective free-living stages: miracidia and cercariae. Schistosomula exposed to SmFES-dsRNA presented a reduction in movement, size and increased mortality. Mice infected with SmFESknocked-down schistosomula exhibited a striking reduction in the area of liver granuloma, an increased rate of immature eggs in the intestine, and female adult worms presented reduced size. Additionally, miracidia hatched from SmFES-knocked-down eggs showed changes in its capability to infect and to sense the snail mucus. Also, SmFES transcript knockdown was stable from miracidia to cercariae. Our findings show that SmFES Tyrosine kinase: (1) is important in schistosomula development and survival; (2) might regulate egg antigens expression, thus responsible for inducing granuloma formation and immunomodulation; (3) has a role in females adult worms development; (4) is essential for miracidia infection capability. Remarkably, this is the first time that a gene is stably knocked-down during three different S. mansoni life stages and that a Tyrosine kinase is implicated in the parasite reproduction and mammalian infection outcome. Accordingly, SmFES should be explored as an alternative to support schistosomiasis treatment and morbidity control.